ANALISIS RISIKO PRODUKSI USAHATANI PADI SAWAH DI DESA SUNGAI BADAK KECAMATAN MESUJI KABUPATEN MESUJI - Asih, Langgeng Tri; Saty, Fadila Marga; Noer, Irmayani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Rice is a staple food source for the Indonesian population. Rice commodity is an agricultural commodity that has a high enough risk and poses a threat to the welfare of rice farmers. The Badak river village is one of the villages that has superior agricultural commodities in Mesuji Regency in the form of rice plants. This research aims to identify the sources of risk faced by farmers in Sungai Badak Village, Mesuji District, Mesuji Regency and analyze the magnitude of the risk impact. The results of the analysis showed that the main sources of risk during planting season 1 were Plant Pest Organisms (OPT) and plant diseases, while the main risk sources in planting season 2 were weather / climate factors. Meanwhile, using the Z-Score shows a risk probability of 30 percent in planting season 1 and 26 percent in planting season 2, while the analysis using the VaR method, the resulting risk impact in planting season 1 is IDR 3,646,801 per hectare, while the risk impact on planting season 2 amounting to IDR 4,030,634, - per hectare.